2021
DOI: 10.3389/fped.2021.681341
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement to Increase Breastfeeding in Preterm Infants: Systematic Review and Meta-Analysis

Abstract: Background and Objective: Due to its numerous health benefits, breast milk (BM) is recommended for preterm infants. Despite such recommendations, the rates of breastfeeding in preterm infants are lower than that in term infants. Quality improvement (QI) bundles increase breastfeeding in preterm infants, but their replication in neonatal intensive care units has had inconsistent outcomes.Methods: We used the Population or Problem, Intervention, Comparison, and Outcomes (PICO) framework to develop our search str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Like human voice, music was one of the preferred auditory stimuli (Standley, 2002). The effects of music therapy on preterm infants have not been conclusively concluded (Chen et al, 2016;O'Toole et al, 2017;Standley, 2012;Yang et al, 2017). In this review, seven included studies compared MSS with music stimulation, and MSS was found to improve preterm infants' behavioural stability versus music stimulation, but there was no solid evidence for improved preterm infants' physiological stability.…”
Section: Discussionmentioning
confidence: 87%
“…Like human voice, music was one of the preferred auditory stimuli (Standley, 2002). The effects of music therapy on preterm infants have not been conclusively concluded (Chen et al, 2016;O'Toole et al, 2017;Standley, 2012;Yang et al, 2017). In this review, seven included studies compared MSS with music stimulation, and MSS was found to improve preterm infants' behavioural stability versus music stimulation, but there was no solid evidence for improved preterm infants' physiological stability.…”
Section: Discussionmentioning
confidence: 87%
“…Using a QI Bundle having several interventions will help to attain desired goals. Systemic Review and Meta-analysis done by Fang et al 7 shows that a total of 12 interventions were used in the QI bundle. The most common is a multidisciplinary expert team developing evidence-based interventions and educating hospital staff and parents.…”
Section: Discussionmentioning
confidence: 99%